The Influence Of Marketing Mix And Brand Awareness On Banking Customers' Interest In Using Home Ownership Credit Services - Sudirjo, Frans; Wahyu Anugrah Manippi; Flora Grace Putrianti; Ratu Nadya Wahyuningratna; Muhammad Syafral (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2024)
The purpose of this study is to ascertain whether social influence, brand awareness, and sharia marketing mix influence the choice of sharia house ownership financing. Customers who select Sharia KPR items make up the research population. Purposive sampling was the method of sampling employed by the researchers. 100 persons were chosen as the sample size by the researchers. In this study, a questionnaire was utilized as an instrument by the researcher to collect the required data. In this study, the researcher used a quantitative research methodology. data interpretation and analysis with SPSS 23.0 software. The analysis results indicate that the three variables studied, namely social, brand awareness, and sharia marketing mix, significantly influence the decision process for selecting sharia bank customers. Brand awareness also has a significant effect, with a significance level of 0.000. Likewise, the sharia marketing mix variable also has a significant impact. In addition, the F test results show that simultaneously, social variables, brand awareness, and the sharia marketing mix have a significant influence on the decision process for selecting sharia bank customers, as evidenced by the F value of 35.5. These findings illustrate that the combination of these factors as a whole has a strong role in shaping customer preferences for Islamic banking products or services. The author suggests that future research add other variables so that this research can further develop for the academic world in the future. So in this case, it is hoped that the bank needs to understand the social conditions of the target market as a form of marketing research to win the sharia banking market share. Can increase brand awareness in the community to win market share.